Pelatihan Peningkatan Perpustakaan Sekolah sebagai Sumber Belajar bagi Lembaga Pendidikan NU Maarif Se Malang Raya - Moh Safii; Setiawan Setiawan; Moch Syahri; Ahmad Munjin Nasih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Realizing According to Law No. 43 of 2007 that every school operates a library that meets the national library standards by taking into account the National Library Standards. Libraries are required to have a collection of textbooks designated as compulsory textbooks in the education unit concerned in sufficient numbers to serve all students and educators. To make this happen, libraries must have competent human resources in their fields. The implementation method used is exposure/lecture, discussion and mentoring via WhatsApp group. The training was held in one day, starting with the pre-test and post-test. The training materials include Library Management, Classification and Cataloging and Library Automation. From the pre-test results, it was found that the category was very poor with an average score of 33 and an average post-test score of 92 with a very satisfying category. From the increase in the pre-test to post-test scores, it was found that this training was able to provide knowledge of school library management based on library automation.